Hukum Progresif dalam Penyelesaian Konflik Sosial: Telaah Hirarki Peraturan Perundang-Undangan dan Peran Hukum Tidak Tertulis pada Kasus Penertiban Pedagang di Kupang - Salfa Putra Neno; Kevy Listiana Fransisca Taneo; Klarinta Victoria Bayfeto; Dewi Astuti S. Saleh (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the application of progressive law in resolving social conflicts between street vendors and the Kupang City Government during enforcement actions in the downtown area. The analysis focuses on the relationship between the hierarchy of legislation—particularly local public order regulations—and unwritten legal sources such as Timorese local wisdom emphasizing deliberation, consensus, and community relations. Using a normative-sociological qualitative approach, the study finds that repressive enforcement reflects a dominance of legalistic approaches, neglecting local values that could strengthen policy legitimacy. Progressive law offers an alternative framework grounded in humanity, social justice, and participatory dialogue. The article argues that harmonizing formal regulations with unwritten norms can produce more humanistic and sustainable enforcement policies.